Comprehensive profile of hip, knee and ankle ranges of motion in professional football players - López-Valenciano, A.; Ayala, F.; Vera-Garcia, F. J.; de Ste Croix, M.; Hernández-Sánchez, S.; Ruiz-Pérez, I.; Cejudo, A.; Santonja, F. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Limited ranges of motion (ROM) have been considered as a primary risk factor for some football injuries, but only a few studies have analyzed differences in lower extremity joints. The main purposes were: 1) to describe the lower extremity ROM profile in professional football players; and 2) to examine differences between goalkeepers and outfield players. METHODS: Eighty-two professional male football players from 4 teams were measured in the 2013 pre-season. Measures of passive hip (flexion with knee flexed [PHFKF] and extended [PHFKE], extension [PHE], abduction [PHA], external [PHER] and internal [PHIR] rotation), knee (flexion [PKF]) and ankle (dorsiflexion with knee flexed [ADFKF] and extended [ADFKE]) ROMs were taken. Magnitude-based inferences exploring differences between player position and limb were made. RESULTS: Overall, 46% of all participants showed restricted PHFKE and/or around 30% showed restricted ADFKF ROM values. Contrarily, most players reported normal PHFKF, PHE, PHIR and PHER as well as PKF ROM scores with percentage values close to 100%. Bilateral meaningful differences for PHA, PHIR and PHER were found in approximately 30% of outfield players and goalkeepers. Statistical analysis found trivial differences between players for PHFKE, PHE, PHIR, PHER, ADFKE and ADFKF. However, moderate differences between players were found for PHFKF, PHA and PKF, with goalkeepers demonstrating higher values than outfield players. CONCLUSIONS: The findings of this study reinforce the necessity of prescribing exercises aimed at improving PHFKE and ADFKF ROM within everyday football training routines. In addition, as some bilateral deficits were observed, unilateral training should be considered where appropriate.